Balancing Conditions for the Relativistic Correction Using Lorentz Acceleration - M. A. Yousef; M. I. El-Saftawy; A. Mostafa (International Journal of Aerospace Engineering, 2023)
In this work, the average effects of the Lorentz acceleration on the charged spacecraft’s orbit are studied encounter with relativistic correction. The relativistic correction as function of the orbital elements, and may be time, is formulated. Lagrange planetary equations are used to calculate the perturbations due to considered perturbing forces. The needed conditions to neutralize the effects of the relativistic corrections, using Lorentz acceleration, are derived. Numerical examples for different kinds of orbits are applied.